The effectiveness of phosphocreatine cardioprotection during vascular surgery in high cardiac risk patients - I. A. Kozlov; D. A.. Sokolov; P. A. Lyuboshevsky (Вестник анестезиологии и реаниматологии)
The objective was to study the occurrence of perioperative cardiovascular complications (CVС) and clinical and laboratory cardioprotection signs in patients treated with phosphocreatine infusion in intraoperative period of vascular surgery.Materials and methods. The study involved 204 patients with high cardiac risk (revised cardiac risk index > 2, risk of perioperative myocardial infarction or cardiac arrest > 1%) who underwent elective vascular surgery. The patients were randomly divided into two groups. Group I patients received intraoperative infusion of phosphocreatine at a dose of 75.9 [69.8–85.7] mg/kg during 120.0 [107.1–132.0] min. Group II was a control group. The occurrence of CVC, the blood level of the cardiospecific troponin I (cTnI) and N-terminal segment of natriuretic B-type prohormone (NT-proBNP) were analyzed. The data were statistically processed, using the Fisher’s exact test, Mann–Whitney test and logistic regression.Results. Perioperative CVС were recorded in 5 (4.9%) patients in group I and in 18 (17.6%) patients in group II (p = 0.007). Intraoperative administration of phosphocreatine was associated with a reduced risk of CVС: OR 0.2405, 95% CI 0.0856–0.6758, p = 0.007. The cTnI level in patients of groups I and II was 0.021 [0.016–0.030] and 0.019 [0.011–0.028] ng/ml (p = 0.102) before surgery, 0.025 [0.020–0.036] and 0.022 [0.015–0.039] ng/ml (p = 0.357) after surgery, 0.025 [0.020–0.031] and 0.028 [0.018–0.033] ng/ml (p = 0.531) before discharge from the hospital. At the same stages, the level of NT-proBNP was 233.5 [195.0–297.5] and 237.8 [171.3–310.1] pg/ml (p = 0.404), 295.5 [257.3–388.0] and 289.0 [217.5–409.5] pg/ml (p = 0.226), 265.5 [204.8–348.5] and 259.6 [171.0–421.6] pg/ml (p = 0.369).Conclusion. In patients with high cardiac risk undergoing vascular surgery, intraoperative phosphocreatine infusion at a total dose of 75.9 [69.8–85.7] mg/kg reduces the risk of perioperative CVC per 24%. Administration of phosphocreatine to patients with high cardiac risk during vascular surgery does not affect perioperative cTnI and NT-proBNP blood levels.